The nematocyst's sting is driven by the tubule moving front. Issue 128 (1st March 2017) - Park, Sinwook; Piriatinskiy, Gadi; Zeevi, Dan; Ben-David, Jonathan; Yossifon, Gilad; Shavit, Uri; Lotan, Tamar
Abstract : The nematocyst is the explosive injection system of the phylum Cnidaria, and is one of the fastest delivery systems found in Nature. Exploring its injection mechanism is key for understanding predator–prey interactions and protection against jellyfish stinging. Here we analyse the injection of jellyfish nematocysts and ask how the build-up of the poly-γ-glutamate (pγGlu) osmotic potential inside the nematocyst drives its discharge. To control the osmotic potential, we used a two-channel microfluidic system to direct the elongating nematocyst tubule through oil, where no osmotic potential can develop, while keeping the nematocyst capsule in water at all times. In addition, the flow inside the tubule and the pγGlu concentration profiles were calculated by applying a one-dimensional mathematical model. We found that tubule elongation through oil is orders of magnitude slower than through water and that the injection rate of the nematocyst content is reduced. These results imply that the capsule's osmotic potential is not sufficient to drive the tubule beyond the initial stage. Our proposed model shows that the tubule is pulled by the high osmotic potential that develops at the tubule moving front. This new understanding is vital for future development of nematocyst-based systems such as osmotic nanotubes and transdermal drug delivery.